1998
DOI: 10.1002/(sici)1097-4636(19981215)42:4<523::aid-jbm7>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface oxidation of polyethylene

Abstract: Since the 1960s ultrahigh molecular weight polyethylene has been a primary bearing material in orthopedic prostheses. Most polyethylene components have been sterilized by exposure to gamma radiation, but in the presence of oxygen this promotes degradation and correlates with component failure in the body. To better understand the mechanism of degradation, we measured oxidation profiles for components shelf aged 5.8 and 10.9 years. Microtomed sections from each component were analyzed for ketones, which are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 21 publications
(21 reference statements)
2
12
0
Order By: Relevance
“…Several investigators have reported on the results of modeling the simultaneous oxygen diffusion and oxidation reactions as a function of depth and time. 19,20,28,29 Several investigators have assumed that the oxygen profile reaches a pseudo steady state in a relatively short time and remains constant thereafter, 19,20 thus simplifying the problem. This assumption is probably reasonable, because the time scale of oxygen diffusion is somewhat shorter than that for the reaction sequence (discussed further below).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Several investigators have reported on the results of modeling the simultaneous oxygen diffusion and oxidation reactions as a function of depth and time. 19,20,28,29 Several investigators have assumed that the oxygen profile reaches a pseudo steady state in a relatively short time and remains constant thereafter, 19,20 thus simplifying the problem. This assumption is probably reasonable, because the time scale of oxygen diffusion is somewhat shorter than that for the reaction sequence (discussed further below).…”
Section: Introductionsupporting
confidence: 60%
“…The predictions of oxygen penetration at 80°C are shown in Figure 2(b) and illustrate the much more rapid transport of oxygen at that elevated temperature. The oxygen-concen- 18 Oxygen diffusivity ϭ 1.14 ϫ 10 Ϫ7 (cm/s) 28 Activation energy for oxygen solubility ϭ Ϫ1.7 (kJ/mol) 18 Activation energy for oxygen diffusion ϭ 36.8 (kJ/mol) 18 tration profile after 1 day (24 h) at 80°C looks very much like the 1-week (7 days) profile at 23°C, keeping in mind that the oxygen solubility at 80°C is marginally lower than that at 23°C, as noted by the surface concentrations. The piece would be essentially saturated to a depth of 5000 m within 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The former appears to be more crystalline than the latter hence confirming the role of the sterilization environment on the morphology of UHMWPE samples. Oxygen can react with the free radicals generated from the chain scission, thus promoting other chain scissions, while in an inert environment, intermolecular cross-linking can protect the material from degradation [21].…”
Section: Discussionmentioning
confidence: 99%
“…This result does not exclude the presence of oxidation species like ketones, alcohols, acids, etc. In fact, many researchers have found that the maximum concentration of these products is several millimeters below the surface [21].…”
Section: Discussionmentioning
confidence: 99%
“…This initiation step turns the chain of the HTC into a free radical. In gamma irradiation processes, this initiation step is ensured by photons [41][42][43]. In this case, to understand how the scission of the C-C bond occurs, molecular reactions in the alkane must be described.…”
Section: Discussionmentioning
confidence: 99%